Note. The Role of Returns Policies in Pricing and Inventory Decisions for Catalogue Goods - Emmons, Hamilton; Gilbert, Stephen M. (Management Science, 1998)
Manufacturers often use returns policies to encourage retailers to stock and price items more aggressively. We focus on the effect that such policies have on both a retailer's and a manufacturer's profits when the retailer must commit prior to the selling season to both a stocking quantity and a price at which to sell an item. Such a commitment is often necessary for retailers who sell primarily through catalogues.